Pemberdayaan Ibu untuk Perbaikan Pola Konsumsi Ikan terhadap Peningkatan Asupan Protein, Kalsium, Zink dan Z-Score Tinggi Badan Menurut Umur pada Anak Stunting - Oslida Martony; Dini Lestrina; Zul Amri (Jurnal Keperawatan Silampari, 2020)
This study aimed to determine the effect of maternal empowerment on improving fish consumption patterns to increase protein intake, calcium, zinc, and Z-score height by age when stunting children. The type of this research is Quasi-Experimental with pre and post-test control group design. The results showed an increase in maternal knowledge, increased intake of protein, calcium, and zinc as well as an increase in TB scores / After the intervention in the case group, compared to the control group, there were no differences in protein, calcium intake and Z-score TB / U, an increase in maternal empowerment increased intake of children stunting and the same as intake of children not stunting. Conclusion There is a significant difference in the average value of protein intake, calcium, zinc, and Z-score before and after providing maternal empowerment interventions to improve fish consumption patterns in children aged 13-36 months. Keywords: Intake, Calcium, Maternal Empowerment, Protein, Zinc, Stunting, Z-Score TB / U